Cross-level relationship of implemented high performance work system and employee service outcomes: The mediating role of affective commitment - Amir Riaz; Hafiz Zahid Mahmood (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
This study examines cross-level relationship between implemented high performance work system (HPWS) and employee service related behaviors along with the mediating effects of employees' affective commitment between this relationship. Although, research studies have confirmed the positive linkage between high performance work system (HPWS) and firm performance. Previous studies were criticized for being management-centric with insights mostly from manufacturing and Western context. Using multilevel approach, this research examines the relationship of bank branch managers' implemented HPWS with (i) employees' service performance and their (ii) service oriented organizational citizenship behavior (OCB) with a particular focus on studying affective commitment as a mediator. For the purpose of this study, data from branch managers of 323 bank branches operating in Punjab, Pakistan and their 1369 front line employees were used. Hierarchical linear modeling (HLM) was applied to test crosslevel hypotheses of this study. Study results revealed that implemented HPWS was significantly related with employees' service performance and their service related discretionary behavior. Further, affective commitment partially mediated both the direct relationships between implemented HPWS and employees' service related behaviors. Empirical findings of this study implied that effectively implemented HPWS by branch managers has the potential to influence affective commitment level of front line employees which further influence their customers service related behaviors. This study contributes by highlighting the potential influence of branch managers' implemented HPWS on service related behaviors of employees.
Keywords: 330; high performance work system (HPWS); service performance; service oriented OCB; banking sector; affective commitment